Scatter in the satellite galaxy SHMR: fitting functions, scaling relations, and physical processes from the IllustrisTNG simulation. Issue 4 (24th March 2022) - Niemiec, Anna; Giocoli, Carlo; Cohen, Ethan; Jauzac, Mathilde; Jullo, Eric; Limousin, Marceau
ABSTRACT: The connection between galaxies and their dark matter haloes is often described with the stellar-to-halo mass relation (SHMR). Satellite galaxies in clusters follow an SHMR distinct from central galaxies because of the environmental processes that they are subject to, and the variety of accretion histories leads to an important scatter in this relation. In this work, we use the suite of magnetohydrodynamical simulations IllustrisTNG to study the scatter in the satellite galaxy SHMR, and extract the parameters that can best allow to understand it. Active galaxies, that represent a very small fraction of cluster galaxies, follow a very different relation than their passive counterparts, mainly because they were accreted much more recently. For this latter population, we find that the distance to the cluster centre is a good predictor of variations in the SHMR, but some information on the galaxy orbital history, such as the distance of closest approach to the host centre, is an even better one, although it is in practice more difficult to measure. In addition, we found that galaxy compactness is also correlated with the SHMR, while the host cluster properties (mass and concentration, formation redshift, mass and size of BCG) do not play a significant role. We provide accurate fitting functions and scaling relations to the scientific community, useful to predict the subhalo mass given a set of observable parameters. Finally, we connect the scatter in the SHMR to the physical processes affecting galaxies in clusters, and how they impact the different satellite subpopulations.